Biochemical and Molecular Characterization of Plant-Parasitic Nematodes - Abrantes, I.M. de O.; Vieira dos Santos, M.C.; Luci, I.; da Conceiçao, P.M.; da Cunha, M. José M.; Santos, M.S.N. de A. (Phytopathologia Mediterranea, 2004)
Nematologists need correct species identification to carry out research, teaching, extension and otheractivities. Therefore, nematode taxonomy must be pursued diligently at all levels. The identification of plant-parasiticnematodes is not always easy and that of some species is especially difficult. Most of the information that nematologistsuse when characterizing and identifying specimens is based on morphological and morphometrical characters. Althoughthese characters are of primary importance, in the last three decades they have been supplemented by biochemical/molecular characters. Biochemical approaches include the separation of proteins (general proteins andisozymes) by one-dimensional gel electrophoresis, isoelectric focusing, two-dimensional gel electrophoresis, and sodiumdodecyl sulphate-capillary gel electrophoresis. Serology has also been found effective in the identification andquantification of nematodes, monoclonal antibodies being a more useful immunological tool than polyclonal antibodies.Identification based on the direct examination of DNA is potentially a more powerful method to characterizeinter- and intra-specific variability. The development of techniques such as the polymerase chain reaction, restrictionfragment length polymorphism, randomly amplified polymorphic DNA, and amplified fragment length polymorphismhas increased the accuracy and speed of nematode characterization/identification. Progress continues to bemade and more and more nematologists are using molecular techniques for diagnostic purposes and to assess geneticvariation.